Sosialisasi Kesehatan dan Keselamatan Kerja (K3) Pada Petugas Pengangkutan Sampah Rumah Tangga di Raberas - Rafi’ah Rafi’ah; Iga Maliga; Ana Lestari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Occupational Safety and Health (K3) is a program created for workers/laborers and entrepreneurs as a preventive measure for the occurrence of work accidents and diseases due to work relations in the work environment by recognizing things that have the potential to cause work accidents and diseases caused by work. work relationship. One type of work that is prone to accidents and occupational health problems is a waste transport officer. The purpose of this community service activity is to increase the knowledge of waste transport officers in Raberas about K3, This service activity involves waste transport officers in the Raberas area, the implementation has been carried out in April-May 2022 and involves 15 garbage collectors. The service is carried out starting from preparation to evaluation, the method used in the service is the method of socialization and application (applicative) directly in the field. The evaluation results show that the level of knowledge of officers about Occupational Health and Safety (K3) is still low, with this community service activity it is expected to increase the knowledge and awareness of waste transport officers at the Raberas TPA when carrying out activities because they have a high risk so they must use appropriate PPE. complete and apply a clean and healthy lifestyle.